2017
DOI: 10.1371/journal.pone.0175025
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 3D lip shapes using facial surface EMG

Abstract: AimThe aim of this study is to prove that facial surface electromyography (sEMG) conveys sufficient information to predict 3D lip shapes. High sEMG predictive accuracy implies we could train a neural control model for activation of biomechanical models by simultaneously recording sEMG signals and their associated motions.Materials and methodsWith a stereo camera set-up, we recorded 3D lip shapes and simultaneously performed sEMG measurements of the facial muscles, applying principal component analysis (PCA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…We notice that Eskes et al (2017) have indeed observed the dissociation we initially predicted, that is, that the EMG amplitude recorded over the OOI was higher during the pronunciation of rounded vowels than during pronunciation of spread vowels, whereas the reverse pattern was observed concerning the ZYG. Paired-samples Wilcoxon signed rank tests revealed a shift in location (pseudomedian) between rounded and spread items for the OOI (β = 24.12,95% CI [15.19,40.77], V = 1184, p < .001) with rounded items being associated with a higher location than spread items.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We notice that Eskes et al (2017) have indeed observed the dissociation we initially predicted, that is, that the EMG amplitude recorded over the OOI was higher during the pronunciation of rounded vowels than during pronunciation of spread vowels, whereas the reverse pattern was observed concerning the ZYG. Paired-samples Wilcoxon signed rank tests revealed a shift in location (pseudomedian) between rounded and spread items for the OOI (β = 24.12,95% CI [15.19,40.77], V = 1184, p < .001) with rounded items being associated with a higher location than spread items.…”
Section: Discussionsupporting
confidence: 73%
“…This analysis also revealed a shift in the inverse direction concerning the ZYG (β = -1.51, 95% CI [-2.94, -0.48], V = 275, p < .001). However, one crucial difference between Eskes et al (2017) design and ours is the complexity of the linguistic material. Whereas Eskes et al (2017) used single phonemes, we chose to use bisyllabic nonwords to increase the ecological validity of the paradigm.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In previous research, we found the following procedure to be optimal for transforming measured sEMG signals into normalised muscle activations 5 – 7 . We first calculated the Willison Amplitude with over sliding windows of 200 ms with maximum overlap: …”
Section: Data Acquisition and Pre-processingmentioning
confidence: 99%